PENGARUH MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN DEEP LEARNING TERHADAP PEMAHAMAN KEARIFAN LOKAL SISWA KELAS IV SEKOLAH DASAR - Karisma Wardhani; Diyanti Jati Pratiwi; Nanda William (STKIP Subang, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model with a deep learning approach on the understanding of local wisdom of Grade IV elementary school students. This research used a quantitative approach with a quasi-experimental design of the nonequivalent control group design type. The subjects consisted of 29 students of Grade IV SDN 3 Jombok as the experimental class and 23 students of Grade IV SDN 1 Tanggaran as the control class. The data collection instrument was a multiple-choice written test (pre-test and post-test) referring to six comprehension indicators according to Anderson & Krathwohl (2001): interpreting, exemplifying, classifying, inferring, comparing, and explaining. Data analysis used the Independent Samples T-Test with SPSS 25.0. The results showed that the average post-test of the experimental class was 75.34, higher than the control class of 62.83. Based on the Independent Samples T-Test, a significance value of 0.002 < 0.05 was obtained, so H0 was rejected and Ha was accepted. This means there is a significant effect of the Problem Based Learning model with a deep learning approach on the understanding of local wisdom of Grade IV elementary school students. The research instrument was declared reliable with a Cronbach’s Alpha of 0.898 (very high category), and all data were proven to be normally distributed and homogeneous.